Addiction and usage of social media among dental students studying in dental institute of Ghaziabad, Uttar Pradesh - Shivangi Varshney; Ipseeta Menon; Ritu Gupta; Anubhav Sharma; Vikram Arora; Sana Bashir (Wolters Kluwer Medknow Publications, 2022)
Background: Social media is frolicking as an utmost priority in today's livelihood, and it is such a milieu today to see people browsing and surfing social networking sites, reading blogs, or chatting by using laptops, mobile phones, or other sophisticated devices anywhere and at any time and enjoying with their favorite social apps - Facebook, WhatsApp, YouTube, etc., Aim: The aim of the study is to assess the knowledge, attitude, and practices of social media usage and addiction among dental students. Materials and Methods: A cross-sectional study was done among 360 students of a dental teaching institute in Uttar Pradesh, India. A questionnaire was prepared which had three sections - related to demographic details and usage and frequency of social media apps based on "Social Media Addiction Scale," developed by Arslan A and Kırık. These were used as the data collection tool to measure social media addiction among dental students. Responses were recorded in 5-point Likert scale - strongly agree, agree, neutral, disagree, and strongly disagree. Data were analyzed by SPSS version 23. Results: Out of total 360 participants, 276 (76.70%) were female while 84 (23.30%) were male. 238 (66.11%) were undergraduates (UGs) followed by 122 (33.89%) postgraduates (PGs). A significantly higher number of UGs were engaged with their patients in personal conversation on social media platform, while a significantly higher number of PGs believed that social media had a positive effect on dentistry. Questions on social media addiction scale by Arslan A and Kırık revealed that out of total study participants, 48.7% of UGs agree on the belief that new media technologies change human life, whereas 39.4% of PGs agree on the same and the result was statistically significant (P ≤ 0.05). Conclusion: Social media networking sites and apps have attracted students in its digital web and hold strong position with new horizons whether in comprehensive or educational, interacting, entertainment, or spending leisure time.